Discovery of a widespread low‐latitude diurnal CO2 frost cycle on Mars. Issue 7 (5th July 2016) - Piqueux, Sylvain; Kleinböhl, Armin; Hayne, Paul O.; Heavens, Nicholas G.; Kass, David M.; McCleese, Daniel J.; Schofield, John T.; Shirley, James H.
Abstract: While the detection of CO2 ice has only been reported outside the Martian polar regions at very high elevation (i.e., Elysium, Olympus Mons, and the Tharsis Montes), nighttime surface observations by the Mars Climate Sounder on board the Mars Reconnaissance Orbiter document the widespread occurrence of atmospherically corrected ground temperatures consistent with the presence of extensive carbon dioxide frost deposits in the dusty low thermal inertia units at middle/low latitudes. Thermal infrared emissivities, interpreted in conjunction with mass balance modeling, suggest micrometer size CO2 ice crystals forming optically thin layers never exceeding a few hundreds of microns in thickness (i.e., 10 −2 kg m −2 ) locally, which is insufficient to generate a measurable diurnal pressure cycle (<<0.1% of the Martian atmosphere). Atmospheric temperatures at middle/low latitudes are not consistent with precipitation of CO2 ice, suggesting that condensation occurs on the surface. The recurring growth and sublimation of CO2 ice on Martian dusty terrains may be an important process preventing soil induration and promoting dynamic phenomena (soil avalanching and fluidization and regolith gardening), maintaining a reservoir of micrometer size dust particles that are mobile and available for lifting. The discovery of this diurnal CO2 cycle represents an important step forward in our understanding of the way the Martian atmosphere interacts with the surface. Key Points: Nighttime surface temperatures consistent with CO2 frost are widespread on Mars Spectral data and mass balance modeling indicate that frost forms micrometer size crystals and optically thin layers The recurring growth and sublimation of CO2 ice is an important process preventing soil induration and maintaining mobile dust reservoirs